Organization, Planning and Control of Marketing Logistics - Olga V. Grishchenko; Vasiliy S. Kireev; Lyudmila I. Dubrova; Marina B. Yanenko; Ruslan Ya. Vakulenko (International Journal of Economics and Financial Issues, 2016)
In the majority of domestic firms physical distribution functions are usually considered to sales. Thus, it is supposed that essential difference between advertising and marketing operations is not available. The marketing logistics as the mechanism of the marketing channel control is concentrated on integration of marketing and logistics functions while maintaining the great value of products and services. In order to evaluate the marketing logistics effectiveness, it is possible to use the concept of “perfect order”. Most companies produce marketing logistics on a functional basis. In its evolution and functional organization of logistics went through three key periods. The first period is characterized by the distribution of logistics functions among the three most major areas of activity: finance, production, and marketing. The second period is characterized by the release of physical distribution functions in an independent direction. Marketing began to implement forecasting sales of finished products, and all other features already belong to physical distribution. It is worth noting that in the second period, the physical distribution of gains recognized on the financing, production and marketing. The third period is characterized by a large extent for the integrated logistics. It is best formed, and in line with market demands structural construction. Also during this period clearly stood out the strategic and operational levels of decision-making. The CEO and the director of logistics make strategic decisions.